The relationship between the way of listening, level of motion expression of the performer and the perception of the piece of music - Dolata, Izabela (Studia Psychologica: Theoria et praxis, 2010)
The aim of the present research was to determine the effect of the artist’s level of motor expression and the subject’s style of listening to musie (active vs passive) on the perception of a piece of musie. Seventy-nine students from the Academy of Musie took part in the experiment. Four experimental situations arose as a result of balancing two variables, each of which were expressed at two levels. The subjects listened to a piece of musie under one of two conditions: active versus passive (for the active condition an instruction intended to activate attentional and imaginational mechanisms was used) and with high versus Iow levels of motor expression on the part of the artist; the sound layer was controlled for in each of the four conditions. After watching the artists’ recordings, the subjects completed the Musie Differential Questionnaire by Andrzej Strzałecki, which is designed to measure the perception of musie along five dimensions: value, execution, mood, emotions and organization. The results showed that active listening had a positive effect on the perception of the value, emotions and organization of the musie, whilst the level of the artist’s motor expression did not have a significant effect on the perception of the musie.